Diabetes and Risks of Right-Sided and Left-Sided Colon Cancer: A Meta-Analysis of Prospective Cohorts - Xiao, Wenxuan; Huang, Jinglong; Zhao, Chuanyi; Ding, Lu; Wang, Xuan; Wu, Bian (Frontiers in Oncology, 2022)
Background and Aims Diabetes is associated with an increased risk of colon cancer (CC). Epidemiologic studies previously reported a higher risk for right-sided colon cancer (RCC) compare to left-sided colon cancer (LCC), although data are conflicting. We performed a meta-analysis to investigate this issue. Methods We systematically searched the PubMed, EMBASE, Web of Science and Cochrane Library database for prospective cohort studies published up to June 2021. Studies were included if they reported site-specific estimates of the relative risk (RR) between diabetes and the risks of RCC and LCC. Random effects meta-analyses with inverse variance weighting were used to estimate the pooled site-specific RRs and the RCC-to-LCC ratio of RRs (RRRs). Results Data from 10 prospective cohort studies, representing 1,642,823 individuals (mainly white) and 17,624 CC patients, were included in the analysis. Diabetes was associated with an increased risk of both RCC (RR =1.35, 95% CI = 1.24-1.47) and LCC (RR = 1.18, 95% CI = 1.08-1.28). After adjusting for major risk factors, individuals with diabetes had a greater risk for RCC than for LCC (RRR = 1.13, 95% CI = 1.02-1.26), with no significant heterogeneity between studies (I2 = 0%). Conclusions This meta-analysis indicates that diabetes is associated with a higher risk for RCC than for LCC. Our findings suggest that colonoscopic surveillance in diabetic patients with careful examination of the right colon is warranted.